Feminist Periodicals v.1, no.1 (1981) - (:unkn) unknown (University of Wisconsin System Women's Studies Librarian's Office, 1981)
Sub-title: A Current Listing of Contents. 53 p.
First issue of table of contents periodical. Statement from p.i: It is our hope that FEMINIST PERIODICALS will serve several purposes: to keep the reader abreast of current topics in feminist literature; to increase readers’ familiarity with a wide spectrum of feminist periodicals; and to provide the requisite bibliographic information should a reader wish to subscribe to a journal or to obtain a particular article at her library or through interlibrary loan.
Keywords: Women's Studies; Periodicals; Tables of Contents; Resources; Gender; Feminism; Women's Periodicals--Index; Lesbian Periodicals--Index